Evolving Definitions of Mental Illness and Wellness - Tara W. Strine, MPH; Satvinder Dhingra, MPH; Lela R. McKnight-Eily, PhD; Carol D. Ryff, PhD; Elsie J. Freeman, MD, MPH; Ronald W. Manderscheid, PhD (Centers for Disease Control and Prevention, 2010)
Understanding of the definitions of wellness and illness has changed from the mid-20th century to modern times, moving from a diagnosis-focused to a person-focused definition of mental illnesses, and from an "absence of disease" model to one that stresses positive psychological function for mental health. Currently, wellness refers to the degree to which one feels positive and enthusiastic about oneself and life, whereas illness refers to the presence of disease. These definitions apply to physical as well as mental illness and wellness. In this article, we build on the essential concepts of wellness and illness, discuss how these definitions have changed over time, and discuss their importance in the context of health reform and health care reform. Health reform refers to efforts focused on health, such as health promotion and the development of positive well-being. Health care reform refers to efforts focused on illness, such as treatment of disease and related rehabilitation efforts.